auto-update(nvim): 2025-02-13 01:54:09
Some checks failed
Deploy Quartz site to GitHub Pages using Nix / build (push) Has been cancelled
Deploy Quartz site to GitHub Pages using Nix / deploy (push) Has been cancelled

This commit is contained in:
Youwen Wu 2025-02-13 01:54:09 -08:00
parent 7c8ce35f66
commit 3d4a68f1f3
Signed by: youwen5
GPG key ID: 865658ED1FE61EC3
3 changed files with 922 additions and 0 deletions

95
; Normal file
View file

@ -0,0 +1,95 @@
#import "@youwen/zen:0.1.0": *
#show: zen.with(
title: "Homework 5",
author: "Youwen Wu",
)
#set heading(numbering: none)
#show heading.where(level: 2): it => [#it.body.]
#show heading.where(level: 3): it => [#it.body.]
#set par(first-line-indent: 0pt, spacing: 1em)
Problems:
2.4: \#4bcde, 5ajq, 6ce, 7a, 9, 10, 12abc
2.5: \#1abc, 3, 10
#outline()
= 2.4
== 4
=== b
$3 + 11 + 19 + dots.c + (8n - 5) = 4n^2 - n$
First we show the base case for $n = 1$.
$ 3 = 4 (1^2) - 1 = 3 $
Now we proceed by induction. Assume $sum _(k=1) ^n (8k-5) = 4(n^2) - n$.
$
sum_(k=1)^(n+1) (8k-5) &= 4((n+1)^2) - (n+1) \
(sum_(k=1)^(n) (8k-5)) + (8(n+1) - 5) &= 4(n^2 + 2n + 1) - n-1 \
(sum_(k=1)^(n) (8k-5)) + 8n + 3 &= 4n^2 - n + 8n + 3 \
(sum_(k=1)^(n) (8k-5)) &= 4n^2 - n \
$
and we know that this is true by our original assumption. So by the PMI, this
is true $forall n in NN$.
=== c
$sum_(i=1)^n 2^i = 2^(n+1) - 2$
For the base case:
$ 2^1 = 2(1 + 1) - 2 \ 2 = 2 $
Assume that
$
sum_(i=1)^n 2^i = 2^(n+1) - 2
$
Proceeding by induction,
$
sum_(i=1)^(n+1) 2^i = 2^(n+1+1) - 2 \
(sum_(i=1)^(n) 2^i) + 2^(n+1) = 2^(n+2) - 2 \
(sum_(i=1)^(n) 2^i) = 2^(n+2) - 2^(n+1) - 2 \
(sum_(i=1)^(n) 2^i) = 2^(n+1) dot (2 - 1) - 2 \
(sum_(i=1)^(n) 2^i) = 2^(n+1) - 2 \
$
So by the PMI, it holds for all $n in NN$.
=== d
$1 dot 1! + 2 dot 2! + 3 dot 3! + dots.c + n dot n! = (n + 1)! - 1$
For the base case: $1 dot 1! = (1 + 1)! - 1 \ 1 = 1$
Assuming the inductive hypothesis,
$
sum^n_(k=1) k dot k! = (n + 1)! - 1 \
$
Now we proceed by induction
$
sum^(n+1)_(k=1) k dot k! = (n + 2)! - 1 \
sum^(n)_(k=1) k dot k! + (n + 1) dot (n+1)! = (n + 2) dot (n + 1)! - 1 \
sum^(n)_(k=1) k dot k! = (n + 2) dot (n + 1)! - (n + 1) dot (n+1)! - 1 \
sum^(n)_(k=1) k dot k! = (n + 1)! dot (n+2 - (n + 1) - 1 \
sum^(n)_(k=1) k dot k! = (n + 1)! - 1 \
$
So by the PMI, this is true for all $n in NN$

View file

@ -0,0 +1,790 @@
#import "@youwen/zen:0.1.0": *
#import "@preview/mitex:0.2.5": *
#show: zen.with(
title: "Homework 5",
author: "Youwen Wu",
)
#set heading(numbering: none)
#show heading.where(level: 2): it => [#it.body.]
#show heading.where(level: 3): it => [#it.body.]
#set par(first-line-indent: 0pt, spacing: 1em)
Problems:
2.4: \#4bcde, 5ajq, 6ce, 7a, 9, 10, 12abc
2.5: \#1abc, 3, 10
#outline()
= 2.4
== 4
=== b
$3 + 11 + 19 + dots.c + (8n - 5) = 4n^2 - n$
#proof[
First we show the base case for $n = 1$.
$ 3 = 4 (1^2) - 1 = 3 $
Now we proceed by induction. Assume $sum _(k=1) ^n (8k-5) = 4(n^2) - n$.
$
sum_(k=1)^(n+1) (8k-5) &= 4((n+1)^2) - (n+1) \
(sum_(k=1)^(n) (8k-5)) + (8(n+1) - 5) &= 4(n^2 + 2n + 1) - n-1 \
(sum_(k=1)^(n) (8k-5)) + 8n + 3 &= 4n^2 - n + 8n + 3 \
(sum_(k=1)^(n) (8k-5)) &= 4n^2 - n \
$
and we know that this is true by our original assumption. So by the PMI, this
is true $forall n in NN$.
]
=== c
#proof[
$sum_(i=1)^n 2^i = 2^(n+1) - 2$
For the base case:
$ 2^1 = 2(1 + 1) - 2 \ 2 = 2 $
Assume that
$
sum_(i=1)^n 2^i = 2^(n+1) - 2
$
Proceeding by induction,
$
sum_(i=1)^(n+1) 2^i = 2^(n+1+1) - 2 \
(sum_(i=1)^(n) 2^i) + 2^(n+1) = 2^(n+2) - 2 \
(sum_(i=1)^(n) 2^i) = 2^(n+2) - 2^(n+1) - 2 \
(sum_(i=1)^(n) 2^i) = 2^(n+1) dot (2 - 1) - 2 \
(sum_(i=1)^(n) 2^i) = 2^(n+1) - 2 \
$
So by the PMI, it holds for all $n in NN$.
]
=== d
#proof[
$1 dot 1! + 2 dot 2! + 3 dot 3! + dots.c + n dot n! = (n + 1)! - 1$
For the base case: $1 dot 1! = (1 + 1)! - 1 \ 1 = 1$
Assuming the inductive hypothesis,
$
sum^n_(k=1) k dot k! = (n + 1)! - 1 \
$
Now we proceed by induction
$
sum^(n+1)_(k=1) k dot k! = (n + 2)! - 1 \
sum^(n)_(k=1) k dot k! + (n + 1) dot (n+1)! = (n + 2) dot (n + 1)! - 1 \
sum^(n)_(k=1) k dot k! = (n + 2) dot (n + 1)! - (n + 1) dot (n+1)! - 1 \
sum^(n)_(k=1) k dot k! = (n + 1)! dot (n+2 - (n + 1) - 1 \
sum^(n)_(k=1) k dot k! = (n + 1)! - 1 \
$
So by the PMI, this is true for all $n in NN$.
]
=== e
#proof[
$1^3 + 2^3 + dots.c + n^3 = [(n(n+1)) / 2]^2$
First checking the base case:
$
1^3 = [(1(1 + 1)) / 2]^2 \
1 = 1
$
Now assume the inductive hypothesis
$ sum_(k=1)^n k^3 = [(n(n+1)) / 2]^2 $
Proceeding by induction,
$
sum_(k=1)^(n + 1) k^3 = [((n+1)(n+2)) / 2]^2 \
sum_(k=1)^(n) k^3 + (n+1)^3 = ((n+1)^2 (n+2)^2) / 4 \
sum_(k=1)^(n) k^3 = ((n+1)^2 (n+2)^2) / 4 - (n+1)^3 \
sum_(k=1)^(n) k^3 = ((n+1)^2 [(n+2)^2 - 4(n+1)]) / 4 \
sum_(k=1)^(n) k^3 = ((n+1)^2 n^2) / 4 \
sum_(k=1)^(n) k^3 = [(n (n+1)) / 2]^2 \
$
So by the PMI it is true $forall n in NN$.
]
== 5
=== a
$n^3 + 5n + 6$ is divisible by 3.
#proof[
Checking the base case,
$
3 | 1^3 + 5(1) + 6 \
3 | 12
$
Now assume the inductive hypothesis.
$
3 | n^3 + 5n + 6
$
Proceeding by induction,
$
3 | (n+1)^3 + 5(n+1) + 6 \
3 | (n+1)^3 + 5(n+1) + 6 \
3 | n^3 + 3n^2 + 3n + 1 + 5n + 5 + 6 \
3 | n^3 + 5n + 6 + 3n^2 + 3n + 6 \
$
By our inductive hypothesis, we know that $3 | n^3 + 5n + 6$. Additionally we
clearly see that $3 | 3n^2 + 3n + 6$ as it can be factored out. So the
$(n+1)^"th"$ case is true and by the PMI, it is true for all $n in NN$.
]
=== j
$3^n >= 1 + 2^n$
#proof[
Base case: $ 3^1 >= 1 + 2^1 \ 3 >= 3 $
Assume the inductive hypothesis
$
3^n >= 1 + 2^n
$
Now proceed by induction
$
3^(n+1) >= 1 + 2^(n+1)
$
We want to show that this statement is always true. Rewrite the left side as
$3 dot 3^n$, then we can derive the following inequality from our inductive
hypothesis:
$
3 dot 3^n >= 3(1 + 2^n) \
3 dot 3^n >= (2 + 1)(1 + 2^n) \
3 dot 3^n >= 2 + 2^(n+1) + 1 + 2^n \
$
And clearly we have
$
2 + 2^(n+1) + 1 + 2^n >= 1 + 2^(n+1)
$
So,
$
3^(n+1) >= 1 + 2^(n+1) + 2 + 2^n >= 1 + 2^(n+1)
$
We have shown that it applies to the $(n+1)^"th"$ case when the $n^"th"$ is
true. Therefore by the PMI it is true $forall n in NN$.
]
=== q
If a set $A$ has $n$ elements, then $cal(P) (A)$ has $2^n$ elements.
#proof[
Just for fun, consider an $n$-tuple that encodes a subset of $A$. Each entry
corresponds to a different element in $A$, and is 1 if that element is in the
subset, and 0 if it is not. Now to count the cardinality of $cal(P)(A)$, we
simply need to count each possible combination of entries in our tuple, as
each tuple corresponds to a unique subset of $A$. Since there are 2
alternatives for each entry and $n$ entries, by the general multiplication
principle, there are $2^n$ variants of this tuple so the cardinality of
$cal(P)(A)$ is $2^n$.
---
Ok now let's do it the annoying way.
#mitext(`
Base Case ($n=0$). \\
If $A$ has $0$ elements, then $A = \varnothing$. Its power set is
\[
\mathcal{P}(A) = \{\varnothing\},
\]
which has exactly one element. Hence
\[
|\mathcal{P}(A)| = 1 = 2^0.
\]
So the statement holds for $n=0$.
Now proceed by induction. Assume the statement is true for some integer $k \ge
0$. That is, suppose that for any set $A$ with $k$ elements, we have
\[
|\mathcal{P}(A)| = 2^k.
\]
Let $B$ be a set with $k+1$ elements. Choose one element $x \in B$, and let $A = B \setminus \{x\}$. Then $A$ has $k$ elements. By the inductive hypothesis,
\[
|\mathcal{P}(A)| = 2^k.
\]
Now observe that any subset of $B$ is either:
\begin{itemize}
\item A subset of $A$ (does not contain $x$), or
\item Of the form $S \cup \{x\}$ where $S \subseteq A$ (does contain $x$).
\end{itemize}
Thus every subset of $A$ gives rise to exactly one subset of $B$ that excludes $x$, and exactly one subset of $B$ that includes $x$. Therefore,
\[
|\mathcal{P}(B)| = |\mathcal{P}(A)| + |\mathcal{P}(A)|
= 2^k + 2^k
= 2 \cdot 2^k
= 2^{k+1}.
\]
Since $B$ was any set with $k+1$ elements, the statement holds for $k+1$. By the principle of mathematical induction, the proof is complete.
`)
]
== 6
=== c
#mitext(`
Let \( n = 5 \). Then:
\[
(5+1)! = 6! = 720 \quad\text{and}\quad 2^{5+3} = 2^8 = 256.
\]
Since \( 720 > 256 \), the inequality holds for \( n = 5 \).
Assume that for some natural number \( n \ge 5 \) the inequality holds for all integers \( m \) with \( 5 \le m \le n \). In particular, assume
\[
(n+1)! > 2^{n+3}.
\]
We must show that
\[
(n+2)! > 2^{(n+1)+3} = 2^{n+4}.
\]
Starting with the left-hand side, we have:
\[
(n+2)! = (n+2)(n+1)!.
\]
Using the inductive hypothesis,
\[
(n+2)! > (n+2) \cdot 2^{n+3}.
\]
Since \( n \ge 5 \), it follows that \( n+2 \ge 7 \). Therefore,
\[
(n+2) \cdot 2^{n+3} \ge 7 \cdot 2^{n+3}.
\]
But clearly,
\[
7 \cdot 2^{n+3} > 2 \cdot 2^{n+3} = 2^{n+4}.
\]
Thus,
\[
(n+2)! > 2^{n+4},
\]
which completes the inductive step.
By the generalized principle of mathematical induction, the inequality
\[
(n+1)! > 2^{n+3}
\]
holds for all natural numbers \( n \ge 5 \).
The inequality is stated to hold for all \( n \ge 5 \). However, for \( n < 5 \) the inequality fails. For instance, when \( n = 4 \):
\[
(4+1)! = 5! = 120 \quad\text{and}\quad 2^{4+3} = 2^7 = 128.
\]
Since \( 120 \) is not greater than \( 128 \), the inequality is false for \( n = 4 \).
`)
=== e
#mitext(`
Let \( n = 4 \). Then:
\[
4! = 24 \quad\text{and}\quad 3 \times 4 = 12.
\]
Since \( 24 > 12 \), the inequality holds for \( n = 4 \).
Assume that for some natural number \( n \ge 4 \) the inequality holds for all integers \( m \) with \( 4 \le m \le n \). In particular, assume that
\[
n! > 3n.
\]
We must show that
\[
(n+1)! > 3(n+1).
\]
Starting with the left-hand side:
\[
(n+1)! = (n+1) \cdot n!.
\]
By the inductive hypothesis, we have:
\[
(n+1)! > (n+1) \cdot 3n.
\]
Since \( n \ge 4 \) (so \( n \ge 2 \)), it follows that:
\[
(n+1) \cdot 3n \ge 3(n+1).
\]
To see this, note that for \( n \ge 2 \) we have:
\[
3n(n+1) = 3(n+1)n > 3(n+1),
\]
because \( n > 1 \). Therefore,
\[
(n+1)! > 3(n+1),
\]
which completes the inductive step.
By the generalized principle of mathematical induction, the inequality
\[
n! > 3n
\]
holds for all natural numbers \( n \ge 4 \).
The claim is that \( n! > 3n \) for all \( n \ge 4 \). However, for some smaller natural numbers the inequality is false. For instance, when \( n = 3 \):
\[
3! = 6 \quad\text{and}\quad 3 \times 3 = 9.
\]
`)
== 7
=== a
#mitext(`
Let \(\{A_i : i \in \mathbb{N}\}\) be an indexed family of sets. Then for every natural number \( n\ge1 \),
\[
\left(\bigcup_{i=1}^{n} A_i\right)^c = \bigcap_{i=1}^{n} A_i^c
\]
and
\[
\left(\bigcap_{i=1}^{n} A_i\right)^c = \bigcup_{i=1}^{n} A_i^c.
\]
For \( n=1 \), we have
\[
\left(\bigcup_{i=1}^{1} A_i\right)^c = A_1^c \quad \text{and} \quad \bigcap_{i=1}^{1} A_i^c = A_1^c.
\]
Thus, the identity holds for \( n=1 \).
Assume that for some \( n \ge 1 \) the statement holds; that is, assume
\[
\left(\bigcup_{i=1}^{n} A_i\right)^c = \bigcap_{i=1}^{n} A_i^c.
\]
We need to show that
\[
\left(\bigcup_{i=1}^{n+1} A_i\right)^c = \bigcap_{i=1}^{n+1} A_i^c.
\]
Notice that
\[
\bigcup_{i=1}^{n+1} A_i = \left(\bigcup_{i=1}^{n} A_i\right) \cup A_{n+1}.
\]
Taking the complement of both sides, and using De Morgan's Law for two sets, we obtain:
\[
\left(\bigcup_{i=1}^{n+1} A_i\right)^c = \left(\left(\bigcup_{i=1}^{n} A_i\right) \cup A_{n+1}\right)^c = \left(\bigcup_{i=1}^{n} A_i\right)^c \cap A_{n+1}^c.
\]
By the induction hypothesis,
\[
\left(\bigcup_{i=1}^{n} A_i\right)^c = \bigcap_{i=1}^{n} A_i^c.
\]
Thus, we have:
\[
\left(\bigcup_{i=1}^{n+1} A_i\right)^c = \left(\bigcap_{i=1}^{n} A_i^c\right) \cap A_{n+1}^c = \bigcap_{i=1}^{n+1} A_i^c.
\]
This completes the inductive step.
By the PMI, we conclude that for every natural number \( n\ge1 \),
\[
\left(\bigcup_{i=1}^{n} A_i\right)^c = \bigcap_{i=1}^{n} A_i^c.
\]
Thus, De Morgan's Laws hold for any indexed family \(\{A_i : i \in \mathbb{N}\}\).
`)
== 9
#mitext(`
Given \(n\) points \(P_1, P_2, \dots, P_n\) in a plane with no three collinear, the number of line segments joining every pair of points is
\[
\frac{n^2 - n}{2}.
\]
For \(n=2\), there is exactly 1 line segment joining the two points. The formula gives
\[
\frac{2^2 - 2}{2} = \frac{4-2}{2} = 1.
\]
So the statement holds for \(n=2\).
Assume that for some \(n \ge 2\), the number of line segments joining \(n\) points is
\[
\frac{n^2 - n}{2}.
\]
Now consider \(n+1\) points. When we add a new point \(P_{n+1}\), this new point can be connected to each of the \(n\) existing points, thereby adding \(n\) new segments. Hence, the total number of segments becomes
\[
\frac{n^2 - n}{2} + n.
\]
Simplify the expression:
\[
\frac{n^2 - n}{2} + n = \frac{n^2 - n + 2n}{2} = \frac{n^2 + n}{2} = \frac{n(n+1)}{2}.
\]
Therefore, by the PMI, the number of line segments joining all pairs of \(n\) points is
\[
\frac{n^2 - n}{2}
\]
for all \(n \ge 2\).
`)
== 10
#mitext(`
The Tower of Hanoi problem with \( n \) disks can be solved in exactly \( 2^n - 1 \) moves.
For \( n = 1 \):
There is only one disk, and it can be moved directly from the source peg to the destination peg in one move.
Since \( 2^1 - 1 = 1 \), the statement holds for \( n = 1 \).
Assume that for some \( k \ge 1 \) the Tower of Hanoi with \( k \) disks can be solved in \( 2^k - 1 \) moves (this is the inductive hypothesis). We now show that a Tower of Hanoi with \( k+1 \) disks can be solved in \( 2^{k+1} - 1 \) moves.
1. Move the top \( k \) disks from the source peg to the auxiliary peg.
By the inductive hypothesis, this takes \( 2^k - 1 \) moves.
2. Move the largest disk (the \((k+1)^\text{th}\) disk) from the source peg to the destination peg.
This requires 1 move.
3. Move the \( k \) disks from the auxiliary peg to the destination peg.
Again by the inductive hypothesis, this requires \( 2^k - 1 \) moves.
\[
\text{Total Moves} = (2^k - 1) + 1 + (2^k - 1) = 2 \cdot 2^k - 1 = 2^{k+1} - 1.
\]
This completes the inductive step.
By the PMI, the Tower of Hanoi with \( n \) disks can be solved in \( 2^n - 1 \) moves.
`)
== 12
=== a
F.
The inductive step assumes that two overlapping sets of $n$ horses share at
least $n1$ horses in common, so that they must all be the same color. But
when $n=1$, two different 1horse sets do not overlap at all, so the argument
that “both sets share a horse of the same color” no longer applies.
=== b
F.
The inductive step is not shown, so there is no justification for the claim
that it is divisible.
=== c
C.
Though the inductive reasoning is right, the base case is not shown, so there
is no reason why this should hold true for all $NN$.
= 2.5
== 1
=== a
#mitext(`
Every natural number \( n \ge 11 \) can be written in the form
\[
n = 2s + 5t,
\]
for some nonnegative integers \( s \) and \( t \).
We verify the statement for the initial numbers:
- \( n = 11 \): \( 11 = 2\cdot 3 + 5\cdot 1 \)
- \( n = 12 \): \( 12 = 2\cdot 1 + 5\cdot 2 \)
- \( n = 13 \): \( 13 = 2\cdot 4 + 5\cdot 1 \)
- \( n = 14 \): \( 14 = 2\cdot 2 + 5\cdot 2 \)
- \( n = 15 \): \( 15 = 2\cdot 5 + 5\cdot 1 \)
Thus, the claim holds for all \( 11 \le n \le 15 \).
Assume as the induction hypothesis that for every integer \( m \) with \( 11 \le m < n \) (where \( n \ge 16 \)) there exist nonnegative integers \( s \) and \( t \) such that
\[
m = 2s + 5t.
\]
Since \( n \ge 16 \), notice that:
\[
n - 2 \ge 14.
\]
Because \( n-2 \) is at least 11 (indeed, \( n-2 \ge 14 \)), the induction hypothesis applies. Therefore, there exist nonnegative integers \( s \) and \( t \) such that:
\[
n - 2 = 2s + 5t.
\]
Then,
\[
n = (n - 2) + 2 = 2s + 5t + 2 = 2(s + 1) + 5t.
\]
If we set \( s' = s + 1 \) (which is clearly a nonnegative integer), we obtain:
\[
n = 2s' + 5t.
\]
Thus, \( n \) can be written in the desired form.
By the PCI, every natural number \( n \ge 11 \) can be written as \( 2s + 5t \) for some nonnegative integers \( s \) and \( t \).
`)
=== b
#mitext(`
Every natural number \( n > 22 \) (i.e. every \( n \ge 23 \)) can be written in the form
\[
n = 3s + 4t,
\]
with integers \( s \ge 3 \) and \( t \ge 2 \).
We prove the statement by complete (strong) induction.
We explicitly verify the claim for a few numbers:
- For \( n = 23 \):
\( 23 = 3 \cdot 5 + 4 \cdot 2 \) (here, \( s = 5 \ge 3 \) and \( t = 2 \ge 2 \)).
- For \( n = 24 \):
\( 24 = 3 \cdot 4 + 4 \cdot 3 \) (here, \( s = 4 \ge 3 \) and \( t = 3 \ge 2 \)).
- For \( n = 25 \):
\( 25 = 3 \cdot 3 + 4 \cdot 4 \) (here, \( s = 3 \ge 3 \) and \( t = 4 \ge 2 \)).
Thus, the statement holds for \( n = 23, 24, 25 \).
Assume that for every integer \( m \) with \( 23 \le m \le n \) (where \( n \ge 25 \)), there exist integers \( s \ge 3 \) and \( t \ge 2 \) such that
\[
m = 3s + 4t.
\]
The number \( n+1 \) can also be written in the form
\[
n+1 = 3s' + 4t',
\]
with \( s' \ge 3 \) and \( t' \ge 2 \).
Since \( n \ge 25 \), observe that
\[
n+1 - 3 = n-2 \ge 23.
\]
By the inductive hypothesis, there exist integers \( s \ge 3 \) and \( t \ge 2 \) such that
\[
n-2 = 3s + 4t.
\]
Then
\[
n+1 = (n-2) + 3 = 3s + 4t + 3 = 3(s+1) + 4t.
\]
Define \( s' = s+1 \) (so that \( s' \ge 3+1 = 4 \ge 3 \)) and let \( t' = t \) (which satisfies \( t' \ge 2 \)). This shows that
\[
n+1 = 3s' + 4t',
\]
with the required conditions.
By the PCI, every natural number \( n > 22 \) (i.e. \( n \ge 23 \)) can be written in the form
\[
n = 3s + 4t,
\]
where \( s \ge 3 \) and \( t \ge 2 \) are integers.
`)
=== c
#mitext(`
Every natural number \( n > 33 \) (i.e. every \( n \ge 34 \)) can be written in the form
\[
n = 4s + 5t,
\]
where \( s \) and \( t \) are integers with \( s \ge 3 \) and \( t \ge 2 \).
We prove the statement by complete induction.
We verify the claim for the first four numbers:
- \( n = 34 \):
\( 34 = 4\cdot 6 + 5\cdot 2 \)
(Here, \( s = 6 \ge 3 \) and \( t = 2 \ge 2 \).)
- \( n = 35 \):
\( 35 = 4\cdot 5 + 5\cdot 3 \)
(Here, \( s = 5 \ge 3 \) and \( t = 3 \ge 2 \).)
- \( n = 36 \):
\( 36 = 4\cdot 4 + 5\cdot 4 \)
(Here, \( s = 4 \ge 3 \) and \( t = 4 \ge 2 \).)
- \( n = 37 \):
\( 37 = 4\cdot 3 + 5\cdot 5 \)
(Here, \( s = 3 \ge 3 \) and \( t = 5 \ge 2 \).)
Thus, the statement holds for \( n = 34, 35, 36, \) and \( 37 \).
Inductive Hypothesis:
Assume that for every integer \( m \) with \( 34 \le m \le n \) (where \( n \ge 37 \)) there exist integers \( s \ge 3 \) and \( t \ge 2 \) such that
\[
m = 4s + 5t.
\]
The number \( n+1 \) can also be written in the form
\[
n+1 = 4s' + 5t',
\]
with \( s' \ge 3 \) and \( t' \ge 2 \).
Since \( n \ge 37 \), we have:
\[
n+1 - 4 = n - 3 \ge 37 - 3 = 34.
\]
Thus, \( n-3 \) is at least 34, and by the inductive hypothesis, there exist integers \( s \ge 3 \) and \( t \ge 2 \) such that
\[
n - 3 = 4s + 5t.
\]
Then,
\[
n+1 = (n-3) + 4 = 4s + 5t + 4 = 4(s+1) + 5t.
\]
Define \( s' = s+1 \) and \( t' = t \). Since \( s \ge 3 \), it follows that \( s' \ge 4 \ge 3 \), and \( t' = t \ge 2 \). Thus, we obtain the required representation:
\[
n+1 = 4s' + 5t',
\]
with \( s' \ge 3 \) and \( t' \ge 2 \).
By the PCI, every natural number \( n > 33 \) (i.e. \( n \ge 34 \)) can be written in the form
\[
n = 4s + 5t,
\]
where \( s \ge 3 \) and \( t \ge 2 \) are integers.
`)
== 3
#mitext(`
Let the sequence \(\{a_n\}\) be defined by
\[
a_1 = 2,\quad a_2 = 4,\quad a_{n+2} = 5a_{n+1} - 6a_n \quad \text{for all } n \ge 1.
\]
Then for all natural numbers \( n \),
\[
a_n = 2^n.
\]
We will prove by complete (strong) induction that for every natural number \( n \), the equality
\[
a_n = 2^n
\]
holds.
- For \( n = 1 \):
\[
a_1 = 2 = 2^1.
\]
- For \( n = 2 \):
\[
a_2 = 4 = 2^2.
\]
Thus, the statement is true for \( n = 1 \) and \( n = 2 \).
Inductive Hypothesis:
Assume that for all natural numbers \( j \) with \( 1 \le j \le n \) (for some \( n \ge 2 \)), we have
\[
a_j = 2^j.
\]
We need to show that \( a_{n+1} = 2^{n+1} \).
Notice that if \( n \ge 2 \), we can apply the recurrence relation with \( j = n-1 \) (since \( n-1 \ge 1 \)):
\[
a_{(n-1)+2} = a_{n+1} = 5a_n - 6a_{n-1}.
\]
By the inductive hypothesis, we know:
\[
a_n = 2^n \quad \text{and} \quad a_{n-1} = 2^{n-1}.
\]
Thus,
\[
a_{n+1} = 5(2^n) - 6(2^{n-1}).
\]
Factor \(2^{n-1}\) from the right-hand side:
\[
a_{n+1} = 2^{n-1}\Bigl(5\cdot 2 - 6\Bigr) = 2^{n-1}(10-6) = 2^{n-1} \cdot 4 = 2^{n+1}.
\]
By the PCI, the equality
\[
a_n = 2^n
\]
holds for all natural numbers \( n \), completing the proof.
`)
== 10
#mitext(`
Every nonempty subset \( S \) of \(\mathbb{Z}^-\) (the set of negative integers) has a largest element.
Let \( S \subseteq \mathbb{Z}^- \) be nonempty. Define the set
\[
T = \{ -s : s \in S \}.
\]
Since every element \( s \) in \( S \) is negative, each \( -s \) is a positive integer. Hence, \( T \) is a nonempty subset of the positive integers \(\mathbb{N}\).
By the well-ordering principle of \(\mathbb{N}\), the set \( T \) has a least element, say \( m \). Thus,
\[
m \in T \quad \text{and} \quad m \le t \quad \text{for all } t \in T.
\]
Since \( m \in T \), there exists an element \( s_0 \in S \) such that
\[
m = -s_0.
\]
We now claim that \( s_0 \) is the largest element of \( S \). To see this, let \( s \) be any element of \( S \). Then \(-s \in T\), and by the minimality of \( m \) we have
\[
m \le -s.
\]
Substituting \( m = -s_0 \), we obtain
\[
-s_0 \le -s.
\]
Multiplying both sides by \(-1\) (which reverses the inequality) gives
\[
s_0 \ge s.
\]
Since \( s \) was an arbitrary element of \( S \), it follows that \( s_0 \) is an upper bound of \( S \) and, being an element of \( S \), is the largest element of \( S \).
Thus, every nonempty subset of \(\mathbb{Z}^-\) has a largest element.
`)

View file

@ -0,0 +1,37 @@
{
pkgs,
typstPackagesCache,
typixLib,
cleanTypstSource,
flakeSelf,
...
}:
let
src = cleanTypstSource ./.;
commonArgs = {
typstSource = "main.typ";
fontPaths = [
# Add paths to fonts here
# "${pkgs.roboto}/share/fonts/truetype"
];
virtualPaths = [
# Add paths that must be locally accessible to typst here
# {
# dest = "icons";
# src = "${inputs.font-awesome}/svgs/regular";
# }
];
XDG_CACHE_HOME = typstPackagesCache;
SOURCE_DATE_EPOCH = builtins.toString flakeSelf.lastModified;
};
in
typixLib.buildTypstProject (
commonArgs
// {
inherit src;
}
)